The Effect of Attention Focus in Errorless and Errorful Practice Conditions on Performance and Learning of Dart Throwing Skill - Hesam Ramezanzade; Marziyeh Doraneh Kord (University of Tehran, 2018)
The aim of this study was to investigate the interactional effect of instruction type of attention focus and two methods of learning (errorless and errorful) on performance and learning of dart throwing skill. It is likely that instruction type of attention focus has a different effect on performance when functional difficulty of task changes. 60 female students were randomly assigned to six groups: internal-errorless, external-errorless, control-errorless, internal-errorful, external-errorful and control-errorful. Errorless groups began their practice with low distance from the target and gradually increased the distance. This was opposite in errorful groups. Internal attention groups focused their attention on elbow and wrist of their throwing hand. External attention groups focused their attention on dart board. After pretest, subjects performed 5 blocks (60 trials each block) and participated in retention test after 48 hours. Factor analysis of variance was used to analyze the data. The results showed no significant differences between internal and external focus in the errorless groups (P>0.05), there was a significant difference among the groups in errorful learning condition (P=0.043). There was a significant difference between errorless and errorful conditions in internal focus groups (in favor of errorless group) (P=0.012). It seems that the challenging role of practice condition is very important in the effectiveness of instruction type of attention focus. It is recommend that errorless learning should be used when using internal attention focus instruction at the beginning of practice.